2012
DOI: 10.5194/acp-12-6983-2012
|View full text |Cite
|
Sign up to set email alerts
|

Can a global model reproduce observed trends in summertime surface ozone levels?

Abstract: Abstract. Quantifying trends in surface ozone concentrations is critical for assessing pollution control strategies. Here we use observations and results from a global chemical transport model to examine the trends (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) in daily maximum 8-h average concentrations in summertime surface ozone at rural sites in Europe and the United States (US). We find a decrease in observed ozone concentrations at the high end of the probabili… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
(88 reference statements)
1
16
0
Order By: Relevance
“…An approach to overcome this complication is to compare long-term ozone observations with model hindcasts forced (or nudged) with observed meteorology. This better isolates model-observation disagreements, and could potentially suggest model improvements (e.g., Pozzoli et al, 2011;Koumoutsaris and Bey, 2012;BrownSteiner et al, 2015;Lin et al, 2015b;Strode et al, 2015;Tilmes et al, 2016;Lin et al, 2017). Overall, such hindcast simulations capture observed decreases in summertime surface ozone in the populated regions of North America and Europe during 1990-2010, but have difficulties simulating the ozone increases measured at remote baseline sites.…”
Section: State Of Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…An approach to overcome this complication is to compare long-term ozone observations with model hindcasts forced (or nudged) with observed meteorology. This better isolates model-observation disagreements, and could potentially suggest model improvements (e.g., Pozzoli et al, 2011;Koumoutsaris and Bey, 2012;BrownSteiner et al, 2015;Lin et al, 2015b;Strode et al, 2015;Tilmes et al, 2016;Lin et al, 2017). Overall, such hindcast simulations capture observed decreases in summertime surface ozone in the populated regions of North America and Europe during 1990-2010, but have difficulties simulating the ozone increases measured at remote baseline sites.…”
Section: State Of Knowledgementioning
confidence: 99%
“…CTMs and SD-CCMs (and nudged CCMs) are often used for performing process-oriented analysis, including interpretation of short-term field measurements (e.g., Law et al, 1998;Liang et al, 2007;Zhang et al, 2008;Telford et al, 2010;Lin et al, 2012a;Wespes et al, 2012) and understanding the causes of ozone variability and long-term trends in observational records, by isolating the roles of emissions and meteorology (Koumoutsaris and Bey, 2012;Lin et al, 2014Lin et al, , 2015Lin et al, , 2017Strode et al, 2015). These models are also used to make chemical forecasts as part of flight planning for field missions (e.g., Fast et al, 2007).…”
Section: Atmospheric Chemistry In Offline Global Modelsmentioning
confidence: 99%
“…However, due to the large computational cost, very few studies have examined the decadal trend in air pollution over large regions such as northern hemisphere. Koumoutsaris and Bey (2012) evaluated the global model performance of O 3 trends simulation (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) through comparison with long-term observed records from EMEP, the World Data Centre for Greenhouse Gases (WD-CGG, http://ds.data.jma.go.jp/gmd/wdcgg/) and the Clean Air Status and Trends Network (US-CASTNET, http://epa. gov/castnet/).…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that O 3 formation depends on both temperature (e.g., Weaver et al, 2009) and humidity and changes in these climate variables must be considered when evaluating trends. For example, Bloomer et al (2010) Zhang et al, 2008), (2) free-running chemistryclimate models (CCMs) that generate their own weather, but are driven with historical emissions (Cooper et al, 2014;Lamarque et al, 2010;Parrish et al, 2014), and (3) multi-decadal hindcast simulations driven with observed meteorology and historical emissions (Brown-Steiner et al, 2015;Koumoutsaris and Bey, 2012;Lin et al, 2015b;Lin et al, 2014;Lin et al, 2017;Strode et al, 2015;Xing et al, 2015). The O 3 trends derived from observations are higher than those from CTMs with constant meteorology, and from free-running CCMs by a factor of two at some sites (e.g., Parrish et al, 2014).…”
Section: Interannual Variability and Trends In Baseline And Usb Omentioning
confidence: 99%